As políticas de valorização docente no Estado de Minas Gerais - Pauliane Romano Cirilo (2012)
This thesis investigates policies for improving teacher profession and their effects on teachers´ work in the Public Education system of the state of Minas Gerais, Brazil. This study intended to understand the emergence of the expression teacher valorization in the Brazilian educational policies and its several meanings. From the literature review analytical categories were arisen in order to perceive teacher valorization. Looking at official documents the research intended to understand how teacher valorization has been embodied in the educational legislation and their different meanings. This research used a database of the Project Teachers´ work in Basic Education in Brazil. The main findings point out that valorization is a current term, at least since last three decades, for teacher policies in Brazil related to teacher education, career, and wages. There is a conceptual dispute over teacher valorization meanings in the Brazilian educational and political contexts. Research data show a complex situation in which it is possible to note that teacher education in service programs are not articulated with teacher education perspective as a continuum process articulated withinitial education. Data also demonstrate a fragmented career, more flexible labor relations, career regulated by performance and very low wages. The findings show that payment by performance although had increased initial salaries compress career levels, and, in some cases, affecting rights previously obtained.